A note on well-posedness of source identification elliptic problem in a Banach space - Ashyralyev, A.; Ashyralyyev, C.; Zvyagin, V.G. (Bulletin of the Karaganda University. Mathematics Series, 2020)
We study the source identification problem for an elliptic differential equation in a Banach space. The exact estimates for the solution of source identification problem in H¨older norms are obtained. In applications, four elliptic source identification problems are investigated. Stability and coercive stability estimates for solution of source identification problems for elliptic equations are obtained.